Kompensasi dan Lingkungan Kerja terhadap Kinerja Karyawan - Karenza Chitara Setiarini; Kustini Kustini (IPM2KPE, 2022)
This study aims to analyze the effect of compensation and work environment on employee performance at PT. Gran Handa Indonesia. This research method is descriptive quantitative with a population of 70 employees in this study. The data collection method that researchers use is a questionnaire. The collected data was carried out by Structural Equation Modeling (SEM) analysis and SmartPLS software. The results showed, a) compensation has a path coefficients value of 0.304901, a T-statistic value of 2.313372 > 1.96 (from table value Zα = 0.05) / P-Value 0.023 <0.05; b) the work environment has a path coefficients value of 0.453660, and a T-statistic value of 4.331262 > 1.96 (from table value Zα = 0.05) / P-Value 0.000 <0.05. In conclusion, the provision of timely compensation can improve the performance of employees of PT. Gran Handa Indonesia. Also, working conditions that are adequate and comfortable enough to work can improve the performance of employees of PT. Gran Handa Indonesia. Keywords: Employee Performance, Compensation, Work Environment